2022
DOI: 10.1186/s12916-022-02527-6
|View full text |Cite
|
Sign up to set email alerts
|

A phase Ib study of camrelizumab in combination with apatinib and fuzuloparib in patients with recurrent or metastatic triple-negative breast cancer

Abstract: Background Strategies to improve activity of immune checkpoint inhibitors for triple-negative breast cancer (TNBC) are needed. Preclinical studies showed that antiangiogenic agents and poly (ADP-ribose) polymerase (PARP) inhibitors might sensitize tumors to immunotherapy. Here, we investigated the tolerability, safety, and preliminary antitumor activity of camrelizumab, an anti-PD-1 antibody, in combination with apatinib, a vascular endothelial growth factor receptor-2 inhibitor, and fuzulopari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…In the ITT population, DCR was 87 %, CBR was 50 %, mPFS was 8.1 months, and mOS was not achieved, with a 1-year OS rate of 68.3 %. The combination of camrelizumab and apatinib with fluzopanib also showed good safety and significant anti-tumor activity [46] . In a phase 1b clinical trial, the combination strategy was used in 32 patients with relapsed or metastatic TNBC.…”
Section: Small Molecule Drugs Targeting Tnbcmentioning
confidence: 99%
“…In the ITT population, DCR was 87 %, CBR was 50 %, mPFS was 8.1 months, and mOS was not achieved, with a 1-year OS rate of 68.3 %. The combination of camrelizumab and apatinib with fluzopanib also showed good safety and significant anti-tumor activity [46] . In a phase 1b clinical trial, the combination strategy was used in 32 patients with relapsed or metastatic TNBC.…”
Section: Small Molecule Drugs Targeting Tnbcmentioning
confidence: 99%
“… 86 Research on the therapeutic effectiveness of PD-1 and PD-L1 inhibitors has mainly been conducted in patients with triple-negative breast cancer. 87 Nevertheless, attempts are currently being made to explore the efficacy of PD-1 and PD-L1 inhibitors in patients with HR+/HER2+ ABC. The combination of T-DM1 and atezolizumab has the potential to enhance the toxicity of anti-HER2 drugs and simultaneously strengthen anti-tumor immunity.…”
Section: Possible New Options For Patients With Hr+/her2+ Abcmentioning
confidence: 99%
“…for neoadjuvant and salvage therapy in TNBC [1,[16][17][18][19] , achieving satisfactory pathological complete response rates and prognoses. Studies have also indicated that PD-1 inhibitors can signi cantly enhance the antitumor e cacy of anthracycline drugs and reduce the risk of TNBC recurrence.…”
Section: Safety Evaluationmentioning
confidence: 99%